Outcomes of Hysterectomy in HIV-Seropositive Women Compared to Seronegative Women - Jennifer Franz; Denise J. Jamieson; Hugh Randall; Cyril Spann (Hindawi Limited, 2005)
Objective. To compare the postoperative complication rates after hysterectomy between HIV-infected patients and HIV-uninfected patients.